Comparison of Tidal Volumes at the Endotracheal Tube and at the Ventilator*. Issue 9 (November 2015) - Kim, Paul; Salazar, Adler; Ross, Patrick A.; Newth, Christopher J. L.; Khemani, Robinder G.
Abstract : Objective: Lung protective ventilation for children with acute respiratory distress syndrome requires accurate assessment of tidal volume. Although modern ventilators compensate for ventilator tubing compliance, tidal volume measured at the ventilator may not be accurate, particularly in small children. Although ventilator-specific proximal flow sensors that measure tidal volume at the endotracheal tube have been developed, there is little information regarding their accuracy. We sought to test the accuracy of ventilator measured tidal volume with and without proximal flow sensors against a calibrated pneumotachometer in children. Design: Prospective, observational. Setting: Tertiary care PICU. Patients: Fifty-one endotracheally intubated and mechanically ventilated children younger than 18 years. Interventions: Tidal volumes were measured at the ventilator, using a ventilator-specific flow sensor, and a calibrated pneumotachometer connected to the SensorMedics 2600A Pediatric Pulmonary Function Cart. Measurements and Main Results: In a pressure control mode of ventilation: median tidal volume measured with the pneumotachometer (9.5 mL/kg [interquartile range, 8.2–11.7 mL/kg]) was significantly higher than tidal volume measured either at the ventilator (8.2 mL/kg [7.1–9.6 mL/kg]) or at the proximal flow sensor (8.1 mL/kg [7.2–10.0 mL/kg]) ( p < 0.001). In pressure regulated volume control mode of ventilation: median tidal volume measured with the pneumotachometer (10.2 mL/kg [8.8–12.4 mL/kg]) was significantly higher than tidal volume measured either at the ventilator (8.0 mL/kg [7.1–9.7 mL/kg]) or at the proximal flow sensor (8.5 mL/kg [7.3–10.4 mL/kg]) ( p < 0.001). These findings were consistent when subgrouped by ventilator type and circuit size. Conclusions: Tidal volume measured either at the endotracheal tube with a proximal flow sensor or at the ventilator with compensation for tubing compliance are both significantly lower than tidal volume measured with a calibrated pneumotachometer. This underestimation of delivered tidal volume may be particularly important when managing children with acute respiratory distress syndrome.